Outcomes and Accountability in Cross-Sector Collaboration on the Implementation of Poverty Reduction Policies in North Kalimantan Province - Iskandar, Iskandar; Sukri, Sukri; Ibrahim, Muh. Akmal; Hasniati, Hasniati (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Poverty is a problem that is generally faced in almost all developing countries, especially densely populated countries like Indonesia. The problem of poverty is considered one of the factors that can hinder the growth of a nation, including Indonesia. One form of poverty in people's lives is through its political aspect, which is shown by the absence of organizations capable of fighting for the interests of the poor. This research aims to analyze outcomes and accountability in cross-sector collaboration in implementing poverty reduction policies in North Kalimantan Province. This research uses a descriptive qualitative approach with data collection methods, namely observation, in-depth interviews, and documentation. The informants in this research are the authorities and are directly involved in cross-sector collaboration on the implementation of poverty reduction policies in North Kalimantan Province. The research results show that there are positive results in the form of increased welfare, education, and access to basic services for the community. Although formal performance assessments at the level of cross-sector coordination have not been carried out, accountability is still maintained through transparent and procedural processes in aid management. This reflects the principle of effective and accountable collaboration in achieving the common goal of reducing poverty.